Design of an evaluation protocol in the area of language for users with dementia type I and II. (REVISTA CIENTÍFICA SIGNOS FÓNICOS, 2020)
INTRODUCTION:The purpose of this research is to design a language evaluation protocol for type I and II Alzheimer's disease for the phonoaudiological approach. The following study focuses mainly on the semantic-lexical and pragmatic components. METHODS:This proposal is a creation of a design for the structure of the language evaluation protocol in Alzheimer's disease in its phase I and II, where it will have an assessment that is given by assessment instruments. RESULTS:Design of the language evaluation protocol in Alzheimer type dementia in its phase II and II, which aims to evaluate the language in its semantic and pragmatic components as they will be altered by this disease. ANALYSIS AND DISCUSSION: The stage of aging as a normal process in humans presents several changes in the higher cognitive processes among this language, these clinical pictures are much more marked when there are underlying pathologies, which generate serious disturbances in the understanding of the same. The speech therapist as a communication professional must have the tools that allow a more detailed assessment of these aspects. CONCLUSIONS:The professionalsin phonoaudiology must be prepared for the constant changes that are being generated in the population, counting on the evaluation and intervention tools that allow to improve the quality of life of the users.
Keywords: dementia; alzheimer disease; phonoaudiology; evaluation; communication and language